PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN BERBANTU APLIKASI ASSEMBLR EDU MATERI INDONESIA KAYA BUDAYA PADA MATA PELAJARAN IPAS DI SEKOLAH DASAR - M. Anggrayni; Wiwik Okta Susilawati; Akhla Alkharimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study develops learning media in the form of learning videos assisted by the assemblr edu application, a development research model. The type of development research or in English Research and Development (R&D) based on the results of the validation test of 3 validators, the validation results carried out by the validator are categorized as very valid with an average of 86.66 categories, namely: language validation gets a very valid category with a percentage of 90.00%, the media category gets a very valid category with a percentage of 86.66%, the content category 83.33% with a very valid category, the practicality assessment is filled in by educators with a percentage of 91.11% categorized as very practical and by students getting a percentage of 91.65% with a very practical category, the effectiveness assessment is seen from the learning outcomes of students who have increased which gets a percentage of 91.30% with a very effective category